Adolescent identity formation - Adams, Gerald R., 1946-; Gullotta, Thomas P., 1948-; Montemayor, Raymond (Newbury Park : Sage Publications, 1992)
"How does identity influence the way adolescents make decisions and cope with stressors? What processes enable the minority adolescent to integrate ethnic identity with other identities into a "meta-identity"? Rooted in the theoretical work of Erikson and Blos, an international team of scholars explores the processes of identity formation, social and behavioral outcomes and management, social contextual factors, and issues of alternative conceptualizations and measurement. Opening with James Marcia's identity status paradigm, the book includes many exciting discussions, including women's identity and Erikson's notions of inner space, Grotevant's process model and how adoptive identity might be studied, the Groningen identity Development Scale, the question of a unitary self, a multidimensional approach to ethnic identity, how cognitive factors intervene in the process of identity formation, and the influence of cognitive identity styles with the ways in which adolescents cope with stress. Students, researchers, and practitioners interested in the latest work on adolescent identity development and its impact on solving adolescents' problems will find this volume a thought-provoking addition to their studies."--BOOK JACKET.
Preface / Gerald R. Adams -- 1. Introduction and Overview / Gerald R. Adams -- 2. The Inner Space and Beyond: Women and Identity / Serena J. Patterson, Ingrid Sochting and James E. Marcia -- 3. A Feminist's Approach to Identity Research / Sally L. Archer -- 4. Identity as an Aspect of Optimal Psychological Functioning / Alan S. Waterman -- 5. Assigned and Chosen Identity Components: A Process Perspective on Their Integration / Harold D. Grotevant -- 6. Identity in Adolescence: Managing Commitments / Harke A. Bosma -- 7. Intrapsychic Dimensions of Identity During Late Adolescence / Jane Kroger -- 8. Ethnic Identity in Adolescence: Process, Context, and Outcome / Jean S. Phinney and Doreen A. Rosenthal -- 9. A Consideration of Intervening Factors in Adolescent Identity Formation / Carol Markstrom-Adams -- 10. A Process Perspective on Identity and Stress Management / Michael D. Berzonsky -- 11. Ego Identity and Adolescent Problem Behavior / Randall M. Jones.
Includes bibliographical references and index.
Keywords: Adolescent Psychology; Ego; Identification (Psychology); Self Concept